Classical Guidance Materials on Career Students Based on INATBKBK Instrument Analysis - Kurniasari, Indah; Farozin, Muh (Jurnal Pendidikan Indonesia, 2021)
Career guidance delivered through classical guidance is important to note in order to support the success of students in careers in the future. Nevertheless, there is still limited material that is appropriate and in accordance with the needs of students that can be used as a reference or basis by the Guidance and Counseling teacher in providing classical guidance in career fields to students. This study aims to find the right material and as needed for classical guidance in the career fields of students. Samples in this study amounted to 353 from 14 public high schools. The research method used is descriptive quantitative through the INATBKBK questionnaire method to collect research data. These 10 topics are the basis of material and references that can be used and developed by counseling guidance teachers in the delivery of career guidance through classical guidance to children. With the existence of concrete material for career guidance, career guidance provided through classical guidance is expected to help students to more mature in preparing for the career they will pursue in the future.